Prevalence and predictors of different patterns of hypertension among adults aged 20-60 years in rural communities of Southeast Nigeria: a cross-sectional study - Rufina N. B. Ayogu; Mmesoma G. Ezeh; Adaobi M. Okafor (BMC, 2021)
Abstract Background Hypertension, a major cardiovascular disease risk factor exists several years without symptoms. Few data exist on prevalence and predictors of hypertension among apparently healthy Nigerian adults. This makes it difficult for policy-makers to concentrate efforts to control emerging health burden of the disease. This study assessed prevalence and predictors of isolated systolic hypertension (ISH), isolated diastolic hypertension (IDH) and combined systolic and diastolic hypertension (CSDH). Methods Cross-sectional survey design was employed in the study of 517 adult participants (20-60 years) in a rural setting. Selection of the respondents was through multistage sampling which involved systematic, proportionate and simple random sampling. Data on socio-demographic characteristics, blood pressure, height, weight, and waist circumference were collected. Frequencies, T-test, analysis of variance and Chi square were used in statistical analysis. Bivariate and multivariate logistic regressions were used to evaluate variables associated with different patterns of hypertension with significance accepted at P < 0.05. Frequencies, percentages, crude and adjusted odd ratios were reported. Statistical Product and Service Solutions version 21.0 was used in statistical analysis. Results ISH (10.6%), IDH (18.2%) and CSDH (37.8%) were observed among the participants. ISH was less likely among 20-29 year-olds (adjusted odds ratio (aOR) = 0.35, 95% confidence interval (C.I.) = 0.13-0.94), 30-39 year-olds (aOR = 0.30, 95% C.I. = 0.11-0.82) and those with abdominal obesity (aOR = 0.12, 95% C.I. = 0.03-0.56). Participants who perceived their health status as good (aOR = 3.80, 95% C.I. = 1.29-11.18) and excellent (aOR = 5.28, 95% C.I. = 1.54-18.07) were respectively 3.80 and 5.28 times more likely to have ISH. Those with secondary education had significantly higher likelihood for IDH (aOR = 2.05, 95% = 1.02-4.14) whereas self-perceived poor health status (aOR = 0.24, 95% C.I. = 0.09-0.65), absence of obesity (aOR = 0.10, 95% C.I. = 0.01-0.81) and general obesity (aOR = 0.35, 95% C.I. = 0.17-0.72) were associated with reduced risk for IDH. Secondary (aOR = 0.60, 95% C.I. = 0.36-0.99) and tertiary (aOR = 0.49, 95% C.I. = 0.28-0.85) education were associated with reduced risk for CSDH but combined obesity (aOR = 4.39, 95% C.I. = 2.25-8.58) increased the risk for CSDH by 4. Conclusion ISH, IDH and CSDH were problems among the adults with age, obesity, self-perception of good/excellent health status and low education level as significant predictors. Health and nutrition education to prevent comorbidities and cerebrovascular accidents are recommended.